Interplay Between Adiponectin, Resistin, Lipoprotein (A) and Prognosis in Middle to old age Female Cases with ST / Non ST Elevation Myocardial Infarction - Shazia Rashid, Javed Anver Qureshi, Rukhshan Khurshid, Ismat Tahira, Sofia Shoukat, Uzma Faryal (Pakistan Journal of Medical & Health Sciences, 2022)
Acute myocardial infarction (AMI) refers to ST-elevated myocardial infarction and non ST elevation myocardial infarction, is the known presentation of coronary artery disease. Study was planned to explore the interplay of the adipokines, resistin / lipoprotein (a) and prognosis in middle to old age female patients with ST / Non ST Elevation Myocardial Infarction. Material and Methods: A cross-sectional study was conducted on 150 middle to old age female patients with acute myocardial infarction (AMI). Consented patients were divided into 2 groups based on ST and Non ST elevation. Duration of study was six months from December 2015 to May 2016. Levels of adiponectin, lipoprotein (a) and resistin were measured. 50 healthy subjects matched for age and gender also participated in study. Results: Mean age of patients with NSTEMI was 58.89 while with STEMI was 50.59 years. Decreased levels of serum adinopectin, resistin and lipoprotein A was observed in female patients with NSTEMI in comparison with these parameters of STEMI, but significantly high level was seen in context of resistin. Positive correlation of age with serum adiponectin and resistin and a negative correlation of age with serum lipoprotein (a) was in female patients with STEMI and NSTEMI. Conclusion: Study found a direct interaction of adiponectin and resistin with strong prognosis of ST and weak prognosis of Non ST elevation of myocardial infarction; whereas lipoprotein (a) showed a strong indirect interaction with age in women with both STEMI and NSTEMI. Keywords: Adiponectin, lipoprotein (a), resistin, STEMI and NSTEMI.